How Walkable are German Cities? New Results from the Field of Walkability Research - Schmitz, Julian; Fina, Stefan; Gerten, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Pedestrian-friendly urban structures motivate people to use active modes of mobility and walk instead of using their car. Active mobility is associated with health-promoting benefits and assumed to support neighbourhood-based social interaction. In this context, walkability assessment tools help urban and transport planning to identify deficiencies for the walkability of urban neighbourhoods and use the results to work towards improvements. The results contribute towards the establishment of indicators to measure development and planning targets with respect to the walkability of urban neighbourhoods and continuous monitoring over time. Based on a newly developed and free available GIS-measurement tool this paper assesses the walkability of the 16 most populated Germany cities at a small scale. The lowest average walkability can be found in the city of Dortmund, while Frankfurt am Main shows the highest values. The paper discusses the methodology and the results for the 16 cities and uses short portrayals of the town planning history and pedestrian infrastructure in Dortmund and Frankfurt am Main to explain possible reasons for the differences in the measurement results.
Keywords: Walkability; Mobility transition; Pedestrians; Public Health; GIS